2022
DOI: 10.3389/fpls.2022.971506
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and transcriptomic analyses reveal the mechanism of sweet-acidic taste formation during pineapple fruit development

Abstract: Pineapple (Ananas comosus L.) is one of the most valuable subtropical fruit crop in the world. The sweet-acidic taste of the pineapple fruits is a major contributor to the characteristic of fruit quality, but its formation mechanism remains elusive. Here, targeted metabolomic and transcriptomic analyses were performed during the fruit developmental stages in two pineapple cultivars (“Comte de Paris” and “MD-2”) to gain a global view of the metabolism and transport pathways involved in sugar and organic acid ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
(121 reference statements)
1
7
0
Order By: Relevance
“…A dramatic drop in organic acids content from YF to MF was observed in our study. Although the exact composition of the organic acids was not determined, previous research has indicated that citric acid is the predominant organic acid in mature pineapple fruit [24,25,26]. In our study, we identified cis-aconitic acid, which is an intermediate in the conversion of citric acid to isocitric acid in the tricarboxylic acid cycle, as it significantly changes with fruit ripening.…”
Section: Discussionmentioning
confidence: 66%
“…A dramatic drop in organic acids content from YF to MF was observed in our study. Although the exact composition of the organic acids was not determined, previous research has indicated that citric acid is the predominant organic acid in mature pineapple fruit [24,25,26]. In our study, we identified cis-aconitic acid, which is an intermediate in the conversion of citric acid to isocitric acid in the tricarboxylic acid cycle, as it significantly changes with fruit ripening.…”
Section: Discussionmentioning
confidence: 66%
“…The only metabolite which presented a positive correlation with taste was GABA, an amino acid not present in proteins. This metabolite has been associated with the development of the sweet-acidic taste in pineapple [28]. It was also shown to correlate with better taste after glycine-betaine treatment in peach [29].…”
Section: Discussionmentioning
confidence: 89%
“…The housekeeping gene Actin was used as an internal control to calculate relative gene expression. Gene expression for each sample was measured by q-PCR using the relative quantification method [ 52 ]. The primers were designed using Primer Premier 6.0 (Premier Biosoft International, Palo Alto, CA, USA) and are listed in Supplementary Table S3 .…”
Section: Methodsmentioning
confidence: 99%